P‐22: Turn‐On Voltage Modulation of Indium‐Gallium‐Zinc‐Oxide Thin‐Film Transistors through Thermal Annealing Processes. Issue 1 (May 2016) - Feng, Zhuoqun; Lu, Lei; Wong, Man; Kwok, Hoi Sing
Abstract : The characteristics of metal‐oxide‐based thin‐film transistors (TFTs) are known to have strong relations with the thermal processes they have gone through. Particularly, the resistivity of the indium‐gallium‐zinc‐oxide (IGZO) film is sensitive to the annealing atmosphere, temperature and cover permeability. A new way of modulating turn‐on voltage (Von ) was proposed by controlling the annealing processes of TFT. The devices will change from enhancement mode to depletion mode with negative Von shift of several volts if they are annealed in nitrogen (N2 ), due to the decreased channel resistivity. And such shift can be recovered in an oxidizing annealing. Considering the absence of high performance p‐type metal‐oxide TFTs, this new method can be used to construct logic circuit based on enhancement and depletion mode n‐type TFTs, exhibiting great potential in assembling system‐on‐panel application.